Experimental Determination of Capillarity of Certain Liquids (Proceedings of Faculty of Civil Engineering, 2023)
The paper describes the basic characteristics of capillarity as one of the basic properties of liquids. The concept of surface tension, the characteristics of cohesion and adhesion forces, the method of determining the height of capillary rise and the most important methods for measuring capillarity in practice are defined. The second part of the paper is based on the creation of an experiments in the Hydrotechnical laboratory of the Faculty of Civil Engineering in Rijeka. The first experiment included experimental measurements of liquid rise heights between two glass plates and the second one was determination of liquid rise heights in small narrow tubes of different diameters for four different types of liquids at their different temperatures.
Keywords: capillarity; surface tension; cohesion; adhesion; experimental research; temperature